Oregon’s History People of the Northwest in the Land of Eden - Michaels, Athanasios (Open textbook library., 2020)
This “open textbook” is a social and cultural history of the people of Oregon representing powerful figures from the dominant Euro-American culture, the marginalized and oppressed, and social and political reformers who shaped the historical legacy of the state. It is a story of the diverse array of immigrants who helped build the state and strengthen it. The title is a recollection of the racial fantasies that European-American settlers created in their expansionist vision of the West and the state of Oregon. Initially the Oregon Territory was built on intolerance and racial exclusivity, but eventually Oregon embraces its diversity, but not without struggle and heartache. Our journey through the past starts with an essential question, “Who are the people of Oregon?”